The discovery of the lymphatic system in the seventeenth century. Part II: the discovery of Chyle vessels. Issue 5 (2nd September 2016) - Suy, Raphael; Thomis, Sarah; Fourneau, Inge
Abstract: In the seventeenth century, opportunities to discover chyle came about through the revival of vivisection. Gaspare Aselli discovered chyle vessels in a living well-fed dog in 1622. He introduced the term 'lacteals' or milky veins. According to Aselli, the lacteals passed through a mesenteric gland which he called 'pancreas'. The 1627 edition of Aselli's booklet was the start of a 'lymphomania', which led to the dissection and vivisection of hundreds of animals, with the University of Leiden being the clear leader in this field. The prominent researchers in Leiden were Jacobus Sylvius and Johannes Walaeus, who performed diverse experiments to support Harvey's theories on systemic circulation, and to find out the correct anatomy and physiology of lacteals and mesenteric glands. Another centre of excellence was Padua, where Veslingius and Wirsüng introduced the idea of the prominent role of the 'real pancreas', and its duct in the transformation of digested food into clear chyle. The idea of the transport of chyle to the liver was an additional support for Galen's theories regarding the function of the liver. Nevertheless, as time went on, there were fewer and fewer believers in Galenic doctrine.